Implication of gap junction coupling in amphibian vitellogenin uptake - Monaco, Maria Eugenia (2007)
The aim of the present study was to investigate the physiological role and the expression pattern of heterologous gap junctions during Xenopus laevis vitellogenesis. Dye transfer experiments showed that there are functional gap junctions at the oocyte/follicle cell interface during the vitellogenic process and that octanol uncouples this intercellular communication. The incubation of vitellogenic oocytes in the presence of biotinylated bovine serum albumin (b-BSA) or fluorescein dextran (FDX), showed that oocytes develop stratum of newly formed yolk platelets. In octanol-treated follicles no sign of nascent yolk sphere formation was observed. Thus, experiments in which gap junctions were downregulated with octanol showed that coupled gap junctions are required for endocytic activity. RT-PCR analysis showed that the expression of connexin 43 (Cx43) was first evident at stage II of oogenesis and increased during the subsequent vitellogenic stages (III, IV and V), which would indicate that this Cx is related to the process that regulates yolk uptake. No expression changes were detected for Cx31 and Cx38 during vitellogenesis. Based on our results, we propose that direct gap junctional communication is a requirement for endocytic activity, as without the appropriate signal from surrounding epithelial cells X. laevis oocytes were unable to endocytose VTG.